Aphrodisias papers 2 : the theatre, a sculptor’s workshop, philosophers, and coin-types : including the papers given at the Third International Aphrodisias Colloquium held at New York University on 7 and 8 April, 1989 (Ann Arbor, MI.)
175 s., [5] cepte katl. pl.